An electric-pulse-assisted stamping process towards springback suppression and precision fabrication of micro channels. (15th March 2022) - Li, Chuanzheng; Xu, Zhutian; Peng, Linfa; Lai, Xinmin
Highlights: An electric-pulse-assisted (EPA) stamping process is developed in this study. The springback of micro channels is suppressed effectively in the EPA stamping. The accelerated stress relaxation leads to the springback suppression effect. The springback angle decreases with the increase of the effective current density. 1 Hz pulsed current leads to effective springback suppression. Abstract: Micro channel features have been widely used in miniaturized products, such as micro reactor, micro heat exchanger, micro fluidic chip. For example, the metallic bipolar plate (BPP) characterized by dense submillimeter channels is a key component of the proton exchange membrane fuel cell (PEMFC). Since several hundreds of BPPs are assembled in a PEMFC stack, a high precision and uniformity of the formed micro channels is required. The micro/meso stamping process has been attracting tremendous attention due to its unique advantages in efficiency and cost. However, the uneven springback of ultra-thin metallic sheet results in evident nonuniformity in the micro channels arrays. In that regard, an electric-pulse-assisted (EPA) stamping method is developed in this research, in which sheet metals are first stamped and electric pulses are subsequently introduced to reduce the springback of formed micro channels. During a series of 7-channel EPA stamping tests, an evident springback suppression is revealed. In the case of 1 Hz electric pulses with the effective current density of 26.56 A/mm 2, 83% of the channel height loss due to the springback is suppressed. Micro hardness tests reveal that the hardening of specimens in the deformation zone is significantly reduced with the introduction of electric pulses. The hardness decreases from 230 to 188 HV due to the accelerated stress relaxation, and the softening effect further leads to lower springback. Based on the analytical calculation and finite element analysis, a combined model is developed to capture the springback suppression effect of electric pulses, which is characterized by the accelerated stress relaxation. The applicability of the EPA stamping is verified and discussed. Graphical abstract: Image, graphical abstract